Polymer, solid electrolyte and preparation method thereof, and solid-state battery

By using components such as multi-branched polyetheramines and specific acrylic derivatives to prepare solid electrolytes with self-healing functions, the problems of polymer matrix crystallization and insufficient mechanical strength in the prior art are solved, and high ionic conductivity and Excellent mechanical properties improve the cycle stability of solid-state batteries.

CN119297392APending Publication Date: 2025-01-10JIANGSU DAOYING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411622538.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

Smart Images

  • Figure CN119297392A_ABST
    Figure CN119297392A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer, a solid electrolyte, a preparation method of the solid electrolyte and a solid-state battery. The solid electrolyte comprises the following raw materials: the polymer, an acrylic acid derivative containing a cyclic group, a photoinitiator, a lithium salt and / or a sodium salt and an inorganic filler, wherein the polymer is generated by mixing and reacting raw materials including polyether amine with a plurality of branched chains, a benzene ring derivative with two terminal aldehyde groups and a benzene ring derivative with terminal aldehyde groups and terminal alkenyl at the same time, and then mixing, rolling and photocuring with other raw materials of the solid electrolyte, so as to prepare the solid electrolyte. Practice shows that the viscoelasticity self-healing polymer not only has relatively strong viscoelasticity and self-healing function, can reduce performance loss to the greatest extent, but also can reduce crystallization, and has good interfacial compatibility, high ionic conductivity and excellent mechanical properties, and a solid-state battery prepared from the viscoelasticity self-healing polymer has excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a polymer, a solid electrolyte, a preparation method thereof, and a solid battery. Background Art

[0002] Solid-state batteries are a major breakthrough in battery technology. The core is to abandon traditional liquid electrolytes and separators and adopt solid electrolytes, which can reduce both the mass and volume of battery packs. In addition, solid-state batteries have excellent fire resistance and the ability to prevent lithium dendrites from penetrating, and have high safety.

[0003] At present, the research on solid-state batteries mainly focuses on polymer-based composite solid electrolytes, which are composed of three parts: polymer matrix (organic matter), lithium / sodium salt and inorganic filler. The polymer matrix is ​​a carrier for ion movement, has a high dielectric constant and good mechanical properties, can reduce the interfacial impedance inside the battery, and make the commercial production of composite solid electrolytes easier. However, currently commonly used polymers, such as polyethylene oxide, polymethyl methacrylate and polyvinylidene fluoride, cannot be well applied to batteries due to problems such as high crystallization or strong film brittleness and mechanical strength that needs to be improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an improved solid electrolyte with low crystallization, good interface compatibility, high ionic conductivity and excellent mechanical properties in view of one or more deficiencies in the prior art.

[0005] The present invention also provides a method for preparing the solid electrolyte and its application in preparing a solid-state battery.

[0006] In order to achieve the above object, a technical solution adopted by the present invention is:

[0007] A solid electrolyte, the raw materials of which include a polymer, an acrylic acid derivative represented by formula (I), a photoinitiator, a lithium salt and / or a sodium salt, and an inorganic filler;

[0008] The raw materials of the polymer include polyetheramine with multiple branches, a compound represented by formula (II), and a compound represented by formula (III);

[0009] In, R a Selected from C 3-20 Aliphatic ring or C 3-20 Heterocyclic, R b , R c Independently selected from H, C 1-6 alkyl;

[0010] In formula (II), R1, R2, R3, and R4 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy;

[0011] In formula (III), R5 and R6 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy, R7, R8 are independently selected from H, C 1-6 alkyl.

[0012] In some embodiments of the present invention, in formula (I), R a Selected from the following substituted or unsubstituted groups: benzene ring, pyridine ring, pyrimidine ring, imidazole ring, C 6-20 Spiral ring, C 6-20 Ring, C 6-20 The bridged ring, substituted with a substituent selected from C 1-6 Alkyl, C 1-6 One or more of the alkoxy groups, R b , R c Independently selected from H, methyl, ethyl, n-propyl or isopropyl.

[0013] Furthermore, in formula (I), R a Selected from benzene ring, pyridine ring, pyrimidine ring, imidazole ring,

[0014] According to a specific aspect of the present invention, the acrylic acid derivative represented by formula (I) may be isobornyl acrylate or the like.

[0015] In some embodiments of the present invention, in formula (II), R1, R2, R3, and R4 are independently selected from H, methyl, ethyl, n-propyl, isopropyl, methoxy, ethoxy, n-propoxy, or isopropoxy.

[0016] In some embodiments of the present invention, in formula (III), R5 and R6 are independently selected from H, methyl, ethyl, n-propyl, isopropyl, methoxy, ethoxy, n-propoxy or isopropoxy, and R7 and R8 are independently selected from H, methyl, ethyl, n-propyl or isopropyl.

[0017] In some embodiments of the present invention, the polyetheramine having multiple branches is a combination of one or more selected from polyetheramine T-403, polyetheramine T-3000, and polyetheramine T-5000.

[0018] In some embodiments of the present invention, the polymer is produced by mixing the polyetheramine having multiple branches, the compound represented by formula (II), and the compound represented by formula (III); further, the mixing reaction is carried out at 15-40°C; further, the mixing reaction is carried out in an anhydrous environment and a solvent.

[0019] In some embodiments of the present invention, a desiccant such as anhydrous magnesium sulfate is added to absorb moisture to form an anhydrous environment.

[0020] In some embodiments of the present invention, the compound represented by formula (II) is produced by mixing a compound represented by formula (II-a) and a compound represented by formula (II-b);

[0021] Furthermore, the mixing reaction is carried out at 15-40°C.

[0022] According to a specific aspect of the present invention, the compound represented by formula (II-a) and the compound represented by formula (II-b) can both be vanillin.

[0023] In some embodiments of the present invention, the compound represented by formula (II-a) and the compound represented by formula (II-b) are reacted in the presence of ferrous sulfate and persulfate in a first solvent; further, the first solvent may be water.

[0024] In some embodiments of the present invention, the compound represented by formula (III) is produced by reacting a compound represented by formula (III-a), epichlorohydrin and a compound represented by formula (III-b); further, the compound represented by formula (III-a) and epichlorohydrin are reacted at 70-120° C., and the mixed reaction is carried out at 100-140° C.;

[0025]

[0026] According to a specific aspect of the present invention, the compound represented by formula (III-a) may be vanillin.

[0027] According to a specific aspect of the present invention, the compound represented by formula (III-b) may be acrylic acid.

[0028] According to some specific aspects of the present invention, the compound represented by formula (III-a) and epichlorohydrin are reacted at 80-100° C. Further, the compound represented by formula (III-a) and epichlorohydrin are reacted in the presence of a catalyst, and the catalyst includes a combination of one or more of benzyltriethylammonium chloride, triethylamine, diethylamine, and triphenylphosphine.

[0029] According to some specific aspects of the present invention, the mixed reaction of adding the compound represented by formula (III-b) is carried out at 110-130° C. Further, the mixed reaction is carried out in the presence of an inhibitor and a catalyst; further, the inhibitor includes at least one of catechol, p-tert-butylcatechol, and catechol, and the catalyst includes a combination of one or more of benzyltriethylammonium chloride, triethylamine, diethylamine, and triphenylphosphine.

[0030] According to some specific aspects of the present invention, the amount of epichlorohydrin added is excessive relative to the amount of the compound represented by formula (III-a).

[0031] In some embodiments of the present invention, the preparation route of the compound represented by formula (III) is as follows:

[0032]

[0033] In some embodiments of the present invention, in the process of preparing the compound of formula (III), after the reaction of the compound of formula (III-a) and epichlorohydrin is completed, excess epichlorohydrin is removed by rotary evaporation, and then an alkaline solution is added, extracted, and the extractant is removed by rotary evaporation to obtain a powdery intermediate, which is then reacted with the compound of formula (III-b) to generate the compound of formula (III).

[0034] In some embodiments of the present invention, in the raw materials of the polymer, by weight, the polyetheramine with multiple branches accounts for 10-50 parts, the compound represented by formula (II) accounts for 5-30 parts, and the compound represented by formula (III) accounts for 10-50 parts.

[0035] In some embodiments of the present invention, in the raw materials of the solid electrolyte, by weight, the polymer accounts for 5-25 parts, the acrylic acid derivative shown in formula (I) accounts for 3-8 parts, the photoinitiator accounts for 0.5-1 part, the lithium salt and / or sodium salt accounts for 10-60 parts, and the inorganic filler accounts for 10-40 parts.

[0036] In some embodiments of the present invention, the raw material of the solid electrolyte also contains an aromatic compound with a terminal vinyl group; further, in parts by weight, the aromatic compound with a terminal vinyl group accounts for 3-8 parts of the raw material of the solid electrolyte; further, the aromatic compound with a terminal vinyl group is styrene and / or allylbenzene.

[0037] In some embodiments of the present invention, the photoinitiator is a combination of one or more selected from methyl benzoylformate, benzil dimethyl ether, 1-hydroxycyclohexane benzophenone, tetraethyl Michler's ketone, diphenylphosphine oxide, and fluorinated diphenyl titanocene.

[0038] In some embodiments of the present invention, the lithium salt and / or sodium salt is a combination of one or more selected from lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, and sodium difluorobis(oxalatophosphate).

[0039] In some embodiments of the present invention, the inorganic filler is a combination of one or more selected from tantalum-doped lithium lanthanum zirconium oxide particles, lithium lanthanum zirconium oxide particles, aluminum oxide particles, titanium dioxide, and silicon dioxide.

[0040] In the present invention, the solid electrolyte can be made relatively thin, which is conducive to reducing the volume of the solid-state battery. In some embodiments of the present invention, the thickness of the solid electrolyte is 0.1-30 μm, further 1-20 μm.

[0041] Another technical solution provided by the present invention is a method for preparing the solid electrolyte described above, the preparation method comprising:

[0042] The polymer, the acrylic acid derivative represented by formula (I), the photoinitiator, the lithium salt and / or the sodium salt and the inorganic filler are mixed, rolled and cured by ultraviolet light to prepare a film-like solid electrolyte.

[0043] In some embodiments of the present invention, the preparation method further includes a thickness adjustment step, and the thickness adjustment step includes: treating the film-shaped solid electrolyte under hot pressing conditions to reduce the thickness.

[0044] Furthermore, the hot pressing conditions include a temperature of 70-90° C. and a pressure of 1-5 MPa.

[0045] Furthermore, the processing time under the hot pressing condition is controlled to be 0.5-5 minutes.

[0046] Another technical solution provided by the present invention is: a solid-state battery, comprising the solid-state electrolyte described above.

[0047] Another technical solution provided by the present invention is: a polymer, wherein the raw materials of the polymer include a polyether amine having multiple branches, a compound represented by formula (II), and a compound represented by formula (III);

[0048] In formula (I), R a Selected from C 3-20 Aliphatic ring or C 3-20 Heterocyclic, R b , R c Independently selected from H, C 1-6 alkyl;

[0049] In formula (II), R1, R2, R3, and R4 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy;

[0050] In formula (III), R5 and R6 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy, R7, R8 are independently selected from H, C 1-6 alkyl.

[0051] Another technical solution provided by the present invention is a solid electrolyte, wherein the preparation method of the solid electrolyte comprises:

[0052] (1) allowing vanillin to react in the presence of ferrous sulfate and persulfate in water with stirring to generate a vanillin dimer;

[0053] (2) reacting vanillin with epichlorohydrin in the presence of a catalyst to generate intermediate 1;

[0054] (3) reacting the intermediate 1 with acrylic acid in the presence of an inhibitor and a catalyst to generate the intermediate 2; then adding a vanillin dimer, a polyetheramine having multiple branches, a desiccant and a solvent (which may be an organic solvent such as dichloromethane) to react, and after the reaction is completed, adding an acrylic acid derivative represented by formula (I) and an aromatic compound having a terminal vinyl group, and mixing them uniformly, removing the desiccant and the solvent to obtain a viscous liquid;

[0055] (4) mixing the obtained viscous liquid, photoinitiator, lithium salt and / or sodium salt and inorganic filler uniformly, rolling and curing with ultraviolet light to obtain a solid electrolyte membrane;

[0056] A heat press process is optionally performed to thin the solid electrolyte membrane.

[0057] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0058] Based on the problems that the polymer matrix used in the existing solid electrolyte has high crystallization or strong film brittleness, and the mechanical strength needs to be improved, the present invention innovatively provides a new type of polymer and applies it to the solid electrolyte. Specifically, the present invention innovatively reacts a polyether amine with multiple branches, a compound represented by formula (II), and a compound represented by formula (III) to generate a polymer matrix with a dynamic imine bond and a catechol-like structure, and further combines it with an acrylic acid derivative with a cyclic structure. Both can be cured under ultraviolet light. It is found in practice that the solid electrolyte prepared in this way not only has strong viscoelasticity and self-healing function, can minimize performance loss, but also can reduce crystallization, has good interface compatibility, high ionic conductivity and excellent mechanical properties, and the solid-state battery prepared with it has excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 The graphs are cycle performance test diagrams of solid-state batteries prepared using the solid-state electrolytes of the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION

[0060] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0061] Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art. Polyetheramine T403 was purchased from Huntsman; LiTFSI powder was purchased from Shanghai Yuanyang New Material Technology Co., Ltd.; LLZTO powder was purchased from Kramar; and the photoinitiator was methyl benzoylformate.

[0062] Example 1

[0063] This embodiment provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0064] (1) 6.02 g of vanillin, 0.20 g of ferrous sulfate heptahydrate, 2.50 g of sodium persulfate and 200 ml of deionized water were mixed evenly, stirred for 0.5 h, washed with hot water three times, and freeze-dried to obtain a gray powder (vanillin dimer) for later use;

[0065] The reaction formula is as follows:

[0066]

[0067] (2) Stir 14.12 g of vanillin, 46.18 g of epichlorohydrin and 1.13 g of benzyltriethylammonium chloride at 90°C for 3 h, remove excess epichlorohydrin by rotary evaporation, and add 0.5 mol / L NaOH aqueous solution to the bottle. Extract the above solution with ethyl acetate three times, remove ethyl acetate by rotary evaporation to obtain a yellow powder, which is set aside;

[0068] The reaction formula is as follows:

[0069]

[0070] (3) In a reaction kettle, add 8.74g of the yellow powder solid obtained in step (2), then add 0.02g of hydroquinone, 0.01g of benzyltriethylammonium chloride and 3.58g of acrylic acid, raise the temperature to 120°C, and react for 3h. Let the reaction kettle stand and cool to room temperature, add 3.17g of the gray powder solid obtained in step (1), then add 8.46g of polyetheramine T403, 10.00g of anhydrous magnesium sulfate and 200g of dichloromethane, stir at room temperature overnight, and confirm that the reaction is complete by the plate result;

[0071]

[0072] After the reaction, the intermediates obtained, such as formula (A), formula (B), and formula (C), are all exemplary structures. The reaction principle is that the aldehyde groups on compound (1) and compound (2) react with the terminal amino groups on polyetheramine T403. Polyetheramine T403 has three terminal amino groups, compound (1) has two terminal aldehyde groups, and compound (2) has one terminal aldehyde group. Therefore, any terminal amino group on polyetheramine T403 can react with the aldehyde group on compound (1) or compound (2). It is possible that all three terminal amino groups react with compound (1), or all react with compound (2); or, one terminal amino group reacts with compound (1), and the other two terminal amino groups react with compound (2); or, two terminal amino groups react with compound (1), and the remaining one terminal amino group reacts with compound (2); in addition, since compound (1) has two terminal aldehyde groups, it can be used as a crosslinking agent to connect two polyetheramines T403; the above reaction process only exemplifies three possible reaction products. In actual reactions, they should exist in the form of a mixture;

[0073] After the above reaction was completed, 5.83 g of isobornyl acrylate was added to the reactor the next day, and after stirring evenly, anhydrous magnesium sulfate was removed by filtration, and dichloromethane was removed by rotary evaporation to obtain a dark brown viscous liquid.

[0074] (4) The viscous liquid obtained in step (3) is mixed evenly with the photoinitiator, LiTFSI powder and LLZTO powder, and then rolled and UV-cured to obtain a solid electrolyte membrane having a thickness of 80 μm. The solid electrolyte membrane is hot-pressed for 1 min at 80° C. and 2 MPa using a flat vulcanizer to obtain a solid electrolyte membrane with a further reduced thickness.

[0075] Example 2

[0076] This embodiment provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0077] (1) 6.02 g of vanillin, 0.20 g of ferrous sulfate heptahydrate, 2.50 g of sodium persulfate and 200 mL of deionized water were mixed evenly, stirred for 0.5 h, washed with hot water three times, and freeze-dried to obtain a gray powder for later use.

[0078] (2) 14.12 g of vanillin, 46.18 g of epichlorohydrin and 1.13 g of benzyltriethylammonium chloride were stirred at 90°C for 3 h, excess epichlorohydrin was removed by rotary evaporation, and 0.5 mol / L NaOH aqueous solution was added to the bottle. The above solution was extracted three times with ethyl acetate, and the ethyl acetate was removed by rotary evaporation to obtain a yellow powder, which was set aside.

[0079] (3) In a reactor, add 8.74g of the yellow powder solid obtained in step (2), then add 0.02g of hydroquinone, 0.01g of benzyltriethylammonium chloride and 3.58g of acrylic acid, heat to 120°C, and react for 3h. Let the reactor stand and cool to room temperature, add 4.23g of the gray powder solid obtained in step (1), then add 9.40g of polyetheramine T403, 10.00g of anhydrous magnesium sulfate and 200g of dichloromethane respectively, stir at room temperature overnight, and determine the completion of the reaction by the plate result. The next day, add 6.32g of isobornyl acrylate to the reactor, stir evenly, filter to remove anhydrous magnesium sulfate, and remove dichloromethane by rotary evaporation to obtain a dark brown viscous liquid.

[0080] (4) The viscous liquid obtained in step (3) is mixed evenly with the photoinitiator, LiTFSI powder and LLZTO powder, and then rolled and UV-cured to obtain a solid electrolyte membrane having a thickness of 80 μm. The solid electrolyte membrane is hot-pressed for 1 min at 80° C. and 2 MPa using a flat vulcanizer to obtain a solid electrolyte membrane with a further reduced thickness.

[0081] Example 3

[0082] This embodiment provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0083] (1) 6.02 g of vanillin, 0.20 g of ferrous sulfate heptahydrate, 2.50 g of sodium persulfate and 200 mL of deionized water were mixed evenly, stirred for 0.5 h, washed with hot water three times, and freeze-dried to obtain a gray powder for later use.

[0084] (2) 14.12 g of vanillin, 46.18 g of epichlorohydrin and 1.13 g of benzyltriethylammonium chloride were stirred at 90°C for 3 h, excess epichlorohydrin was removed by rotary evaporation, and 0.5 mol / L NaOH aqueous solution was added to the bottle. The above solution was extracted three times with ethyl acetate, and the ethyl acetate was removed by rotary evaporation to obtain a yellow powder, which was set aside.

[0085] (3) In a reactor, add 8.74g of the yellow powder solid obtained in step (2), then add 0.02g of hydroquinone, 0.01g of benzyltriethylammonium chloride and 3.58g of acrylic acid, heat to 120°C, and react for 3h. Let the reactor stand and cool to room temperature, add 4.23g of the gray powder solid obtained in step (1), then add 9.40g of polyetheramine T403, 10.00g of anhydrous magnesium sulfate and 200g of dichloromethane respectively, stir at room temperature overnight, and determine the completion of the reaction by the plate result. The next day, add 3.16g of styrene and 3.16g of isobornyl acrylate to the reactor, stir evenly, filter to remove anhydrous magnesium sulfate, and remove dichloromethane by rotary evaporation to obtain a dark brown viscous liquid.

[0086] (4) The viscous liquid obtained in step (3) is mixed evenly with the photoinitiator, LiTFSI powder and LLZTO powder, and then rolled and UV-cured to obtain a solid electrolyte membrane having a thickness of 80 μm. The solid electrolyte membrane is hot-pressed for 1 min at 80° C. and 2 MPa using a flat vulcanizer to obtain a solid electrolyte membrane with a further reduced thickness.

[0087] Example 4

[0088] This embodiment provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0089] (1) 6.02 g of vanillin, 0.20 g of ferrous sulfate heptahydrate, 2.50 g of sodium persulfate and 200 mL of deionized water were mixed evenly, stirred for 0.5 h, washed with hot water three times, and freeze-dried to obtain a gray powder for later use.

[0090] (2) 14.12 g of vanillin, 46.18 g of epichlorohydrin and 1.13 g of benzyltriethylammonium chloride were stirred at 90°C for 3 h, excess epichlorohydrin was removed by rotary evaporation, and 0.5 mol / L NaOH aqueous solution was added to the bottle. The above solution was extracted three times with ethyl acetate, and the ethyl acetate was removed by rotary evaporation to obtain a yellow powder, which was set aside.

[0091] (3) In a reaction kettle, add 8.74g of the yellow powder solid obtained in step (2), then add 0.02g of hydroquinone, 0.01g of benzyltriethylammonium chloride and 4.28g of methacrylic acid, heat to 120°C, and react for 3h. The reaction kettle is left to cool to room temperature, 4.23g of the gray powder solid obtained in step (1) is added, and then 9.40g of polyetheramine T403, 10.00 anhydrous magnesium sulfate and 200g of dichloromethane are added respectively, stirred at room temperature overnight, and the reaction is completed by the plate result. The next day, 2.53g of styrene and 3.79g of isobornyl acrylate are added to the reaction kettle, stirred evenly, filtered to remove anhydrous magnesium sulfate, and dichloromethane is removed by rotary evaporation to obtain a dark brown viscous liquid.

[0092] (4) The viscous liquid obtained in step (3) is mixed evenly with the photoinitiator, LiTFSI powder and LLZTO powder, and then rolled and UV-cured to obtain a solid electrolyte membrane having a thickness of 80 μm. The solid electrolyte membrane is hot-pressed for 1 min at 80° C. and 2 MPa using a flat vulcanizer to obtain a solid electrolyte membrane with a further reduced thickness.

[0093] Comparative Example 1

[0094] This example provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0095] (1) Commercially available polyethylene oxide (PEO) was vacuum dried at 80°C for 24 hours.

[0096] (2) PEO, LiTFSI powder and LLZTO powder were added to 15 mL of DMF solvent and stirred at room temperature for 5 h to obtain an electrolyte solution. The solution was poured into a crystallization dish and dried at 55 °C for 24 h to obtain a solid electrolyte membrane.

[0097] Comparative Example 2

[0098] This example provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0099] (1) Commercially available polyvinylidene fluoride (PVDF) powder was vacuum dried at 80°C for 24 hours.

[0100] (2) PVDF, LiTFSI powder and LLZTO powder were added to 15 mL of DMF solvent and stirred at room temperature for 5 h to obtain an electrolyte solution. The solution was poured into a crystallization dish and dried at 55 °C for 24 h to obtain a solid electrolyte membrane.

[0101] Comparative Example 3

[0102] This example provides a solid electrolyte and a preparation method thereof, the preparation method comprising:

[0103] (1) 6.02 g of vanillin, 0.20 g of ferrous sulfate heptahydrate, 2.50 g of sodium persulfate and 200 mL of deionized water were mixed evenly, stirred for 0.5 h, washed with hot water three times, and freeze-dried to obtain a gray powder for later use.

[0104] (2) 14.12 g of vanillin, 46.18 g of epichlorohydrin and 1.13 g of benzyltriethylammonium chloride were stirred at 90°C for 3 h, excess epichlorohydrin was removed by rotary evaporation, and 0.5 mol / L NaOH aqueous solution was added to the bottle. The above solution was extracted three times with ethyl acetate, and the ethyl acetate was removed by rotary evaporation to obtain a yellow powder, which was set aside.

[0105] (3) In a reaction kettle, add 8.74g of the yellow powder solid obtained in step (2), then add 0.02g of hydroquinone, 0.01g of benzyltriethylammonium chloride and 3.58g of acrylic acid, heat to 120°C, and react for 3h. Let the reaction kettle stand and cool to room temperature, add 3.17g of the gray powder solid obtained in step (1), then add 8.46g of polyetheramine T403, 10.00g of anhydrous magnesium sulfate and 200g of dichloromethane respectively, stir at room temperature overnight, and determine the completion of the reaction by the plate result. The next day, add 5.83g of hydroxyethyl acrylate to the reaction kettle, stir evenly, filter to remove anhydrous magnesium sulfate, and remove dichloromethane by rotary evaporation to obtain a dark brown viscous liquid.

[0106] (4) The viscous liquid obtained in step (3) is mixed evenly with the photoinitiator, LiTFSI powder and LLZTO powder, and then rolled and UV-cured to obtain a solid electrolyte membrane having a thickness of 80 μm. The solid electrolyte membrane is hot-pressed for 1 min at 80° C. and 2 MPa using a flat vulcanizer to obtain a solid electrolyte membrane with a further reduced thickness.

[0107] Performance Testing

[0108] Test method:

[0109] Tensile strength test of solid electrolyte (GB / T 1040.2): The solid electrolyte is cut into standard dumbbell-shaped specimens and the tensile strength is tested using a polymer tensile strength testing machine.

[0110] Ion conductivity test of solid electrolyte: CR2032 button battery assembly was used to assemble steel sheet / solid electrolyte membrane steel sheet battery, and the test was conducted using Chenhua 660E electrochemical workstation. The impedance (R / Ω) of the solid electrolyte membrane was obtained by EIS AC impedance test method, and the thickness (d / cm) and area (S / cm) of the electrolyte membrane were measured. 2 ), using the formula Calculate the ionic conductivity (mS·cm -1 ).

[0111] Battery internal resistance and cycle performance test:

[0112] Battery Assembly:

[0113] (a) Preparation of positive electrode

[0114] The positive electrode active material LiCoO2, the binder PVDF, and the conductive carbon black are mixed in a weight ratio of 90:5:5, N-methylpyrrolidone is added, and the mixture is stirred with a stirrer in a dehumidified room until the mixture becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on an aluminum foil with a thickness of 10 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients, and then dried in an oven at 120°C for 2 hours, and then rolled and cut to obtain a positive electrode sheet with a thickness of 80 μm.

[0115] (b) Preparation of negative electrode

[0116] The metal lithium sheet is used as the negative electrode.

[0117] (c) Preparation of solid-state batteries

[0118] The negative electrode sheet, solid electrolyte and positive electrode sheet are stacked in sequence, with auxiliary tabs and aluminum-plastic film sealing materials.

[0119] After assembling the solid-state battery, it was tested using the Chenhua 660E electrochemical workstation.

[0120] The test results are shown in Table 1.

[0121] Table 1

[0122]

[0123] From the comparison of the examples and comparative examples in Table 1, it can be seen that the tensile strength of the solid electrolyte of the present invention is significantly enhanced, and the inherent characteristics of the elastomer play a role, which comprehensively improves the comprehensive performance of the solid electrolyte. The ionic conductivity of the prepared battery is improved by 1 order of magnitude, indicating that the polymer material with self-healing function has a certain conductivity, which also lays a foundation for the improvement of cycle performance;

[0124] Among them, Comparative Example 3 is roughly the same as Example 1, with only some conditions changed, such as the use of aliphatic hydroxyethyl acrylate as an active diluent. However, practice has shown that its performance is poor, which makes the overall polymer with "T"-type polyetheramine as the main structure. The overall resin has insufficient rigidity, the physical properties of the prepared solid electrolyte are poor, and ultimately the electrochemical performance is also poor.

[0125] from Figure 1It can be seen from the cycle performance test results of the obtained solid-state battery that the solid electrolyte prepared by the present invention: the cycle performance of Examples 1-4 is significantly higher than that of the comparative example. This result is consistent with the test results of ionic conductivity. Moreover, the self-healing solid electrolyte prepared by the present invention has a catechol-like structure, which can give the material excellent adhesion properties, and the interface between the solid electrolyte membrane and the positive and negative electrodes of the battery is more tightly bonded under the action of hot pressing. In summary, the solid electrolyte not only has a self-healing function, but also has excellent elasticity and adhesion, which is of great significance for improving the safety and cycle performance of the battery.

[0126] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0127] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A solid electrolyte, characterized in that The raw materials of the solid electrolyte include a polymer, an acrylic acid derivative represented by formula (I), a photoinitiator, a lithium salt and / or a sodium salt, and an inorganic filler; The raw materials of the polymer include polyetheramine with multiple branches, a compound represented by formula (II), and a compound represented by formula (III); In formula (I), R a Selected from C 3-20 Aliphatic ring or C 3-20 Heterocyclic, R b , R c Independently selected from H, C 1-6 alkyl; In formula (II), R1, R2, R3, and R4 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy; In formula (III), R5 and R6 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy, R7, R8 are independently selected from H, C 1-6 alkyl.

2. The solid electrolyte according to claim 1, characterized in that In formula (I), R a Selected from the following substituted or unsubstituted groups: benzene ring, pyridine ring, pyrimidine ring, imidazole ring, C 6-20 Spiral ring, C 6-20 Ring, C 6-20 The bridged ring, substituted with a substituent selected from C 1-6 Alkyl, C 1-6 One or more of the alkoxy groups, R b , R c Independently selected from H, methyl, ethyl, n-propyl or isopropyl.

3. The solid electrolyte according to claim 2, characterized in that In formula (I), R a Selected from benzene ring, pyridine ring, pyrimidine ring, imidazole ring, 4. The solid electrolyte according to claim 1, characterized in that In formula (II), R1, R2, R3, and R4 are independently selected from H, methyl, ethyl, n-propyl, isopropyl, methoxy, ethoxy, n-propoxy, or isopropoxy; and / or, In formula (III), R5 and R6 are independently selected from H, methyl, ethyl, n-propyl, isopropyl, methoxy, ethoxy, n-propoxy or isopropoxy, and R7 and R8 are independently selected from H, methyl, ethyl, n-propyl or isopropyl.

5. The solid electrolyte according to claim 1, characterized in that The polyetheramine with multiple branches is a combination of one or more selected from polyetheramine T-403, polyetheramine T-3000, and polyetheramine T-5000.

6. The solid electrolyte according to claim 1, characterized in that The polymer is produced by mixing the polyetheramine with multiple branches, the compound represented by formula (II) and the compound represented by formula (III); further, the mixing reaction is carried out at 15-40°C.

7. The solid electrolyte according to claim 1, characterized in that The compound represented by formula (II) is produced by mixing a compound represented by formula (II-a) and a compound represented by formula (II-b); Furthermore, the mixing reaction is carried out at 15-40°C.

8. The solid electrolyte according to claim 1, characterized in that The compound represented by formula (III) is prepared by reacting the compound represented by formula (III-a) and epichlorohydrin, and then reacting the compound represented by formula (III-b); further, the compound represented by formula (III-a) and epichlorohydrin are reacted at 70-120° C., and the mixed reaction is carried out at 100-140° C.; 9. The solid electrolyte according to claim 1, characterized in that In terms of weight, in the raw materials of the polymer, the polyetheramine with multiple branches accounts for 10-50 parts, the compound represented by formula (II) accounts for 5-30 parts, and the compound represented by formula (III) accounts for 10-50 parts.

10. The solid electrolyte according to claim 1, characterized in that In terms of weight, the raw materials of the solid electrolyte include 5-25 parts of polymer, 3-8 parts of acrylic acid derivatives represented by formula (I), 0.5-1 parts of photoinitiator, 10-60 parts of lithium salt and / or sodium salt, and 10-40 parts of inorganic filler.

11. The solid electrolyte according to claim 1 or 10, characterized in that: The raw materials of the solid electrolyte also contain aromatic compounds with terminal vinyl groups; further, in terms of weight, the aromatic compounds with terminal vinyl groups account for 3-8 parts of the raw materials of the solid electrolyte; further, the aromatic compounds with terminal vinyl groups are styrene and / or allylbenzene.

12. The solid electrolyte according to claim 1 or 10, characterized in that: The photoinitiator is a combination of one or more selected from methyl benzoylformate, benzil dimethyl ether, 1-hydroxycyclohexane benzophenone, tetraethyl Michler's ketone, diphenylphosphine oxide, and fluorinated diphenyl titanocene; And / or, the lithium salt and / or sodium salt is a combination of one or more selected from lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, and sodium difluorobis(oxalatophosphate); And / or, the inorganic filler is a combination of one or more selected from tantalum-doped lithium lanthanum zirconium oxide particles, lithium lanthanum zirconium oxide particles, aluminum oxide particles, titanium dioxide, and silicon dioxide; And / or, the solid electrolyte has a thickness of 0.1-30 μm, further 1-20 μm.

13. A method for preparing a solid electrolyte according to any one of claims 1 to 12, characterized in that: The preparation method comprises: The polymer, the acrylic acid derivative represented by formula (I), the photoinitiator, the lithium salt and / or the sodium salt and the inorganic filler are mixed, rolled and cured by ultraviolet light to prepare a film-like solid electrolyte.

14. The method for preparing a solid electrolyte according to claim 13, characterized in that: The preparation method further includes a thickness adjustment process, which includes: treating the film-shaped solid electrolyte under hot pressing conditions to reduce the thickness.

15. A solid-state battery, characterized in that: The solid-state battery comprises the solid-state electrolyte according to any one of claims 1 to 11.

16. A polymer, characterized in that The raw materials of the polymer include polyetheramine with multiple branches, a compound represented by formula (II), and a compound represented by formula (III); In formula (I), R a Selected from C 3-20 Aliphatic ring or C 3-20 Heterocyclic, R b , R c Independently selected from H, C 1-6 alkyl; In formula (II), R1, R2, R3, and R4 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy; In formula (III), R5 and R6 are independently selected from H, C 1-6 Alkyl, C 1-6 Alkoxy, R7, R8 are independently selected from H, C 1-6 alkyl.